Characterisation of myocardial injury via t1 mapping in early reperfused myocardial infarction and its relationship with global and regional diastolic dysfunction - Mohd Shah, Azarisman Shah; Carbone, Angelo; Shirazi, Mitra; Bradley, Julie; Teo, Karen S.L; Worthley, Matthew I.; Worthley, Stephen G. (Elsevier Ltd, 2016)
Background Cardiovascular magnetic resonance (CMR) advances in imaging techniques, permits the ability to accurately characterise tissue injury post myocardial infarction. Pre-contrast T1 mapping enables this through measurement of pre-contrast T1 relaxation times. We investigate the relationship between T1 characterisation of myocardial injury with global and regional diastolic function. Methods Revascularised acute myocardial infarction patients with normal left ventricular (LV) systolic function on TTE were assessed by 1.5T CMR. Acute regional diastolic wall motion abnormalities, global diastolic function measurements, acute segmental damage fraction with LGE and mean segmental pre-contrast T1 values were assessed on matching short axis slices. Results Forty-four patients were analysed. Mean LVEF was 62.1 ± 9.4%. No difference between NSTEMI (22/44) and STEMI in mean pre-contrast T1 values of infarcted (1025.0 ± 109.2 vs 1011.0 ± 81.6ms, p = 0.70), adjacent (948.3 ± 45.3 vs 941.1 ± 46.6 ms, p = 0.70) and remote (888.8 ± 52.8 vs 881.2 ± 54.5 ms, p = 0.66) segments was detected. There was no correlation between pre-contrast T1 of infarcted segments with global diastolic dysfunction (E/A, r 2 = 0.216, p = 0.06; S/D, r 2 = 0.243, p = 0.053; E/E’, r 2 = 0.240, p = 0.072), but there was significantly positive, moderate correlation with circumferential diastolic strain rate, (r 2 = 0.579, p < 0.01) with excellent agreement and reproducibility. Conclusion Cardiac magnetic resonance evaluation of pre-contrast T1 values revealed no difference between NSTEMI and STEMI patients in terms of tissue characterisation post-myocardial infarction. However, pre-contrast T1 of infarcted tissue is significantly correlated with regional diastolic circumferential strain rate.